PENINGKATAN KUALIFIKASI GURU DALAM SITUASI KETERBATASAN TENAGA PENGAJAR DI SDIT AL-FATHIMIYAH - Siti Fatimah Azzahra; Hafshah Azizah; Hinggil Permana; Vita Nur Lintang Fitriyani (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2022)
This study analyzes the tactics of improving teacher qualifications at SDIT Al Fathimiyah in the face of limited teacher manpower.A qualitative case study approach was used using data collection techniques through in-depth interviews, personal observation in the field, and analysis of a large number of supporting documents.The results of the study reveal that the tactics applied by the school include regular internal training, external collaboration using other educational forums, and integration of art elements, especially music, in the learning process to increase motivation & teaching effectiveness. The primary challenges encountered were limited operational rules, high workload of teachers juggling multiple roles, and limited access to certified training. Nonetheless, the school continued to innovate to form creative solutions. This research provides simple and theoretical insights that can be used as a basis for policy formulation to improve the quality of education in schools using limited resources